El comercio internacional y la produccion de frijol en Colombia - Luna González, Carlos Adolfo; Janssen, W. (1990)
A historical review of bean imports in Colombia as of 1984 is presented as well as an analysis of the conditions that lead to their occurrence. The effect of foreign bean trade on national production, mainly carried out by small farmers, and on domestic prices is also analyzed, emphasizing price level and stability. There is evidence of the sensitivity of the traditional sector to the macroeconomic, intersectorial, and international forces. The bean producing sector has proven to be productive and has quickly responded to changes in price. After the demand for beans is corrected by market availability, it also shows a growing trend. In spite of beans being a staple, their market is already segmented. It is feasible to implement greater scope and long term development policies so traditional crops like beans become rural development foundations. Some theoretical perspectives regarding price stability are also included. (CIAT)